The Role of The Concept Of "Education and Discipline" In the Family in Eastern and Western Countries (Journal of Pedagogical Inventions and Practices, 2022)
The foundations of upbringing are laid in the family. It is a school of life that nurtures all human relationships and children that should be formed in a child. The necessary opportunities will be created for them to acquire a profession according to their interests, to have a perfect knowledge of the rules of ethics and to follow them.